2016
DOI: 10.1037/a0039881
|View full text |Cite
|
Sign up to set email alerts
|

Psychosociocultural structural model of college success among Latina/o students in Hispanic-serving institutions.

Abstract: Previous studies of college entrance and graduation have identified strong ethnic identity, cultural congruity, and low acculturative stress as protective factors for academic persistence among Latina/o college students. However, lacking in the literature is a more differentiated and complete understanding of the complex relationships between cultural and psychosocial factors that may lead to college success for students attending Hispanic-Serving Institutions (HSIs) of higher education. Proposing a structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 67 publications
(101 reference statements)
3
44
0
Order By: Relevance
“…In doing so, educators would know when to make effective referrals to trained counselors, who could then provide help to students. Another implication for counselors is to consider social networking for increasing students' sense of belonging, as well as helping to train faculty on cultural awareness and diversity (Chun, Marin, Schwartz, Pham, & Castro‐Olivo, ). Given that our study found that cultural and diversity factors positively predicted academic motivation, counselors should also work with students to address ways to positively cope with academic stress, such as talking about the source of the stress and adopting a positive attitude.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In doing so, educators would know when to make effective referrals to trained counselors, who could then provide help to students. Another implication for counselors is to consider social networking for increasing students' sense of belonging, as well as helping to train faculty on cultural awareness and diversity (Chun, Marin, Schwartz, Pham, & Castro‐Olivo, ). Given that our study found that cultural and diversity factors positively predicted academic motivation, counselors should also work with students to address ways to positively cope with academic stress, such as talking about the source of the stress and adopting a positive attitude.…”
Section: Discussionmentioning
confidence: 99%
“…Second, researchers should consider conducting studies exploring ways counselors could better promote positive psychological and physical health among students through campus‐wide programming (Chun et al, ). Given that many colleges and universities are asking their counseling centers to do more with less, these types of programs might represent an efficient use of physical resources and staff time.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research on campus climate at HSIs has mixed findings regarding academic and sociosychological development for Latino students. HSIs have lower graduation rates compared with institutions that are more selective and have greater resources; however, HSIs graduate a large proportion of Latinos in higher education (Garcia, 2013(Garcia, , 2016 There is evidence that attending an HSI not only leads Latinos to develop a strong sense of racial-ethnic identity but also increases their sense of belonging and positive perceptions about their academic abilities (Arbelo-Marrero & Milacci, 2016;Chun, Marin, Schwartz, Pham, & Castro-Olivo, 2016;Guardia & Evans, 2008). For example, Latino students attending an HSI with 75% Latino enrollment had higher aspirations for their academic success, attributed to their strong sense of belonging and positive perceptions of their campus climate (Arbelo-Marrero & Milacci, 2016).…”
Section: Sense Of Belonging and Racial Microaggressionsmentioning
confidence: 99%
“…I was never taught that culture has any relationship with the learning process of my students. Ethnic identity, cultural congruity, and acculturation were new terms I learned that play an important part in the success of my students (6,7). Furthermore, Yosso's Cultural Wealth Model represents how students of color access and experience college based on six forms of cultural capital that include aspirational, linguistic, familial, social, navigational, and resistance (8).…”
Section: Inclusive Excellence Starts After a Personal Introspectionmentioning
confidence: 99%